Reseña de Jucker, A. & Taavitsainen, I. (eds.) (2008). Speech Acts in the History of English - Richard, María Etelvina (Pragmalingüística, 2008)
<!--[if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> Se trata de una reseña de Jucker, A. & Taavitsainen, I. (eds.) (2008). Speech Acts in the History of English. <!--[if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->